A scenario-based approach for probabilistic load flow analysis of electric vehicle charging and photovoltaic integration in distribution systems: An Indonesian case study - Jimmy Trio Putra; M. Isnaeni Bambang Setyonegoro; Sasongko Pramono Hadi; Sarjiya (Results in Engineering)
Deploying Electric Vehicle Charging Stations (EVCS) and Photovoltaic (PV) generation into distribution networks supports clean energy goals and the electrification of transport. However, these technologies introduce operational uncertainties that are often underestimated in conventional studies. This paper addresses the lack of realistic uncertainty modeling by constructing probabilistic profiles for EVCS loads and PV generation based on real-world data. A scenario-based approach is conducted to evaluate the impact of these uncertainties on system performance. The results show that voltage fluctuations occurred on each bus during the simulation. PV integration reduces power losses; however, integrating the demand for EVCS increases them. The average correlation between EVCS load and bus voltage is strongly negative, with -0.7452 for the 33-bus system and -0.4622 for the 69-bus system. These values indicate that increased EVCS demand tends to reduce voltage levels across the network, reflecting the sensitivity of bus voltages to charging activities. This study can serve as a basis for research on integrating the EVCS load and PV generation, which exhibit uncertain characteristics.